Gram-Scale Preparation of Acyl Fluorides and Their Reactions with Hindered Nucleophiles - Tryniszewski, Michał; Barbasiewicz, Michał (Synthesis, 2021)
A series of acyl fluorides was synthesized at 100 mmol scale using phase-transfer-catalyzed halogen exchange between acyl chlorides and aqueous bifluoride solution. The convenient procedure consists of vigorous stirring of the biphasic mixture at room temperature, followed by extraction and distillation. Isolated acyl fluorides (usually 7–20 g) display excellent purity and can be transformed into sterically hindered amides and esters when treated with lithium amide bases and alkoxides under mild conditions.
Keywords: acyl fluorides; phase-transfer catalysis; directed ortho-metalation; amides; esters